7x+4=2(3x+1)-x+7

Simple and best practice solution for 7x+4=2(3x+1)-x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+4=2(3x+1)-x+7 equation:


Simplifying
7x + 4 = 2(3x + 1) + -1x + 7

Reorder the terms:
4 + 7x = 2(3x + 1) + -1x + 7

Reorder the terms:
4 + 7x = 2(1 + 3x) + -1x + 7
4 + 7x = (1 * 2 + 3x * 2) + -1x + 7
4 + 7x = (2 + 6x) + -1x + 7

Reorder the terms:
4 + 7x = 2 + 7 + 6x + -1x

Combine like terms: 2 + 7 = 9
4 + 7x = 9 + 6x + -1x

Combine like terms: 6x + -1x = 5x
4 + 7x = 9 + 5x

Solving
4 + 7x = 9 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
4 + 7x + -5x = 9 + 5x + -5x

Combine like terms: 7x + -5x = 2x
4 + 2x = 9 + 5x + -5x

Combine like terms: 5x + -5x = 0
4 + 2x = 9 + 0
4 + 2x = 9

Add '-4' to each side of the equation.
4 + -4 + 2x = 9 + -4

Combine like terms: 4 + -4 = 0
0 + 2x = 9 + -4
2x = 9 + -4

Combine like terms: 9 + -4 = 5
2x = 5

Divide each side by '2'.
x = 2.5

Simplifying
x = 2.5

See similar equations:

| -7a+6a=-8a+14 | | x-8y=-59 | | 14a^2b^3+15ab^3-9b^3=0 | | 3.5q-2.5-2.7q=-0.2q-2.5 | | 9x^2-6x+3-2x-11x^2= | | -x+2+10x=-2+5x+32 | | (x-5)(x+1)+5=0 | | 12k^3q^4-4k^2q^5-kq^6=0 | | 7x^2-5-11x^2+10+8x= | | -(5y+1)-(-4y-3)=-2 | | -4x-16=18 | | x+(x+12)+(4x-36)=1056 | | -9x^2+5+10x^2-13x= | | 9p^2-18p+8=0 | | 4x+11=39 | | 15x^2-94x+24=0 | | 7x^4+4=0 | | -9x^2-8+5x+11x^2-13x= | | 8x^4=0 | | -(7y+5)-(-6y-7)=-6 | | t-16=-32 | | 234=10+2x | | 9(4x-4)=3(12x+3) | | 9x^2-5+2x-3x^2-13= | | -7x=27 | | -1.3a=-10.4 | | 234=10x | | 4(3v+3)+v= | | 27t^3-64x^6=0 | | 234=10+x | | x-2=x+24 | | -4u+3+u-4= |

Equations solver categories